High-fat diets induce inflammatory IMD/NFκB signaling via gut microbiota remodeling in Drosophila - Wang, Jun; Gu, Jiaojiao; Yi, Jianhan; Li, Jie; Li, Wen; Zhai, Zongzhao (Frontiers in Cellular and Infection Microbiology, 2024)
High-fat diets (HFDs), a prevailing daily dietary style worldwide, induce chronic low-grade inflammation in the central nervous system and peripheral tissues, promoting a variety of diseases, including pathologies associated with neuroinflammation. However, the mechanisms linking HFDs to inflammation are not entirely clear. Here, using a Drosophila HFD model, we explored the mechanism of HFD-induced inflammation in remote tissues. We found that HFDs activated the IMD/NFkB immune pathway in the head through remodeling of the commensal gut bacteria. Removal of gut microbiota abolished such HFD-induced remote inflammatory response. Further experiments revealed that HFDs significantly increased the abundance of Acetobacter malorum in the gut, and the reassociation of this bacterium was sufficient to elicit strong inflammatory response in remote tissues. Mechanistically, Acetobacter malorum produced a greater amount of peptidoglycan (PGN), a welldefined microbial molecular pattern that enters the circulation and remotely activates an inflammatory response. Our results thus show that HFDs trigger inflammation mediated by a bacterial molecular pattern that elicits host immune response.